EVALUASI PROGRAM KARTU JAKARTA PINTAR (KJP) PLUS DI SEKOLAH DASAR KECAMATAN MAKASAR JAKARTA TIMUR - andri wijaya; Abdul Rahman A. Ghani; Sri Yuliawati (Jurnal Penelitian dan Penilaian Pendidikan, 2023)
In general, this thesis aims to obtain information about the KJP Plus program at the Makassar District Elementary School, East Jakarta. This evaluation uses the CIPP model approach (Context, Input, Process, and Product). Data collection techniques through documentation studies, and questionnaires. The data analysis technique in this evaluation method uses a quantitative-descriptive approach with stages consisting of: data reduction, data presentation, and drawing conclusions. The results of the evaluation concluded that: (1). The context of the implementation of the KJP Plus program at the Makassar District Elementary School, East Jakarta is in accordance with the applicable provisions in the KJP Plus program. (2) The input from the implementation of the KJP Plus program is appropriate in supporting the success of the KJP plus program at the Makassar District Elementary School, East Jakarta. (3) The implementation of the KJP Plus program at the Makassar District Elementary School, East Jakarta has been going well, but there needs to be improvements in the aspect of reporting the use of KJP plus funds. (4) The achievement of the implementation of the KJP Plus program at the Makassar District Elementary School, East Jakarta during the COVID-19 pandemic was not yet optimal, especially in meeting the needs of students, especially in supporting educational needs